Detection of Lyme Borrelia in Questing Ixodes scapularis (Acari: Ixodidae) and Small Mammals in Louisiana - LEYDET, BRIAN F. (2014)
Lyme borreliosis is caused by spirochetes from the Borrelia burgdorferi sensu lato species complex. In the United States, B. burgdorferi sensu stricto (s.s.; Johnson, Schmid, Hyde, Steigerwalt, and Brenner) is the most common cause of human Lyme borreliosis. With >25,000 cases reported annually, it is the most common vector-borne disease in the United States. Although approximately 90% of cases are contained to the northeastern and Great Lake states, areas in Canada and some southern states are reporting rises in the number of human disease cases. Louisiana records a few cases of Lyme each year. Although some are most certainly the result of travel to more endemic areas, there exists evidence of locally acquired cases. Louisiana has established populations of the vector tick, Ixodes scapularis (Say), and a wide variety of potential reservoir animals, yet Lyme Borrelia has never been described in the state. Using culture and polymerase chain reaction, we investigated the presence of Lyme Borrelia in both mammals and questing ticks at a study site in Louisiana. Although culture was mostly unsuccessful, we did detect the presence of B. burgdorferi s.s. DNA in 6.3% (11 of 174) of ticks and 22.7% (five of 22) of animal samples. To our knowledge, this is among the first evidence documenting B. burgdorferi s.s. in Louisiana. Further investigations are required to determine the significance these findings have on human and animal health.